Optical Scattering Detection And Characterisation Of Crystal Originated Particles In Czochralski-Grown Silicon Wafers - Lee , Wah Pheng (2005)
In microelectronics, cost reduction and improved performance requires device miniaturization in the ultra large scale integration (ULSI) chip. The consequence is that minute structural defects and contamination, not previously considered, on the silicon wafer become increasingly critical to the device reliability and manufacturing yield. While the contamination may be removed from the silicon surface by wet cleaning, the grown-in defects will not be cleaned. The latter includes the truncated voids which appear as pits on the polished surface, and are often known as the crystal-originated "particles" (COPs).